Nursing of an ovarian cancer patient with intestinal obstruction treated with Traditional Chinese Medicine rectal drip therapy (中药肛门滴入疗法治疗1例卵巢癌肠梗阻患者的护理体会) - LYU Yingying (吕莹莹); LIU Shuhong (刘书红); ZHAO Yan (赵燕) (中西医结合护理, 2023)
To summarize the Traditional Chinese Medicine rectal drip therapy and nursing management of an ovarian cancer patient with intestinal obstruction. Nurses had enhanced the maintenance of gastric tube and monitoring on drainage fluid during the gastrointestinal decompression treatment. In addition of intravenous nutrition therapy, the traditional Chinese Medicine rectal drip therapy was carried to relive the nausea and abdominal distension of the patient. (本文总结1例中药肛门滴入治疗卵巢癌肠梗阻患者的护理经验。在持续胃肠减压, 保持胃管通畅, 观察引流液的性质、量、颜色, 给予静脉营养支持治疗的基础上, 基于中医辨证, 采用中药肛门滴入疗法, 有效缓解患者恶心、腹胀症状, 对提高患者生存质量有着积极意义。)